Hair Transplant for Eyebrow Restoration - Rajput, Rajendrasingh J. (Indian Journal of Plastic Surgery, 2021)
Eyebrow restoration can be best done with individual single hair follicles grafts harvested by FUE. Understanding the male and female eyebrow allows us to plan an aesthetic reconstruction, requiring 70 to 120 grafts. Selection of donor hair, angle of placement, alignment and direction within the rows influences the results, as does scarring and perfusion of the skin. Details of planning, technique, anesthesia and postoperative care, as well as drawbacks of older methods, are discussed in the article.
Keywords: Eyebrow; FUE; Transplant